Quantitative trait loci (QTL) for cowpea resistance to flower bud thrips (Megalurothrips sjostedti Trybom) - Sobda, G.; Boukar, O.; Tongoona, P.B.; Ayertey, J.; Offei, K.S. (2017)
Cowpea flower bud thrips causes about 80% yield losses in cowpea. Host plant resistance is the most easy and durable solution to the damaging effects caused by this insect. However, resistance to thrips is quantitatively inherited, thus less amenable through conventional breeding. The objective of this study was to identify QTL associated with resistance to cowpea flower bud thrips in a bid to facilitate the improvement of cowpea resistance to thrips. A mapping population consisting of 150 F2 plants derived from cross between the highly resistant SANZI (female) and the highly susceptible VYA (male) was screened under artificial infestation in the screen house. Thrips damage scores were used as the parameter for resistance. A total of 232 polymorphic Single Nucleotide Polymorphism (SNP) markers were used for genotyping of F2 and the parents. Three significant QTLs for thrips resistance Fthp28, Fthp87 and Fthp129were detected on chromosomes 2, 4 and 6 accounting for 24.5, 12.2 and 6.5 % of the total phenotypic variation respectively. Transgressive segregation was observed towards the susceptible phenotype. Both additive and non-additive QTL effects were observed with additive effects being predominant. Further studies to validate these QTL for their useful exploitation in marker-assisted breeding programme are essential.